Contact angle hysteresis of a drop spreading over metal surfaces; MATEC Web of Conferences; Vol. 84 : Interfacial Phenomena and Heat Transfer (IPHT 2016) - Kuznetsov G. V. Geny Vladimirovich (2016, 2016)
Title screen